How to attract donations: the case of US NGOs in international development - Nunnenkamp, Peter; Öhler, Hannes (The journal of development studies, 2012)
We assess the determinants of private donations across a large sample of US based NGOs with foreign aid activities. Our results show that donations do not depend in the expected way on publicly available information on NGO characteristics that reveal an efficient and targeted use of funds, notably the efficiency price of NGO aid and the degree of specialisation. Private donors rather rely on the frequently offered option to designate donations to preferred purposes - even though this is unlikely to tie the NGOs' hands.